Chemical and photonic interactions in vitro and in vivo between fluorescent tracer and nanoparticle-based scavenger for enhanced molecular imaging - T. Gulin-Sarfraz; E. Pryazhnikov; J. Zhang; L. Khiroug; J.M. Rosenholm (Materials Today Bio, 2019)
We hereby present a concept of scavenging excess imaging agent prior to a diagnostic imaging session, consequently allowing for enhanced contrast of signals originating from the tissue area of interest to the signals originating from systemic imaging agent residues. In our study, a prospective silica core–shell nanoparticle-based scavenger was designed and explored for its feasibility to scavenge a specific imaging agent (tracer) in the bloodstream. The developed tracer–scavenger system was first investigated under in vitro conditions to ensure proper binding between tracer and scavenger is taking place, as confirmed by Förster/fluorescence resonance energy transfer studies. In vivo, two-photon imaging was utilized to directly study the interaction of the scavenger particles and the tracer molecules in the vasculature of mice. To our knowledge, a methodological solution for in vivo differentiation between signals, originating from tissue and blood, has not been presented elsewhere. Keywords: Silica nanoparticles, Imaging agents, Contrast enhancement, Tracer, Scavenger, Molecular imaging, Diagnostic imaging